2008
DOI: 10.1002/uog.5361
|View full text |Cite
|
Sign up to set email alerts
|

Transobturator mesh for cystocele repair: a short‐ to medium‐term follow‐up using 3D/4D ultrasound

Abstract: 21 (range, SD, 7.0) mm in length.Conclusions At 10-month follow-up the Perigee procedure seems to be safe and effective for cystocele repair, with a satisfaction rate of 78%. In some women recurrence may occur due to dislodgment of the superior anchoring arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
0
18
0
3
Order By: Relevance
“…We do not yet know if these modifications improve anatomical outcome. However, Shek et al 12 performed postoperative threedimensional (3D)-4D translabial ultrasonography in 46 patients with cystocele who underwent a transobturator mesh procedure with suture of the mesh to the bladder base. They observed, at a mean follow-up of 10 months, recurrence in six patients (13%), including in five cases cystocele recurrence craniodorsal to the mesh associated with a marked change in orientation of the mesh axis on Valsalva, implying dislodgement of the superior anchoring arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not yet know if these modifications improve anatomical outcome. However, Shek et al 12 performed postoperative threedimensional (3D)-4D translabial ultrasonography in 46 patients with cystocele who underwent a transobturator mesh procedure with suture of the mesh to the bladder base. They observed, at a mean follow-up of 10 months, recurrence in six patients (13%), including in five cases cystocele recurrence craniodorsal to the mesh associated with a marked change in orientation of the mesh axis on Valsalva, implying dislodgement of the superior anchoring arms.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is already used as an informative and objective complementary tool in the evaluation of urinary incontinence and POP 9 . Moreover, polypropylene vaginal meshes as well as polypropylene suburethral slings are hyperechogenic 10 , and different authors have reported the feasibility of analyzing them by standardized two-dimensional (2D) ultrasonography 11,12 . We conducted this study to investigate whether 2D postoperative ultrasonography of polypropylene meshes coupled with a careful clinical examination could help to improve the assessment of mesh retraction and to understand the mechanism of recurrence observed after TVM repair of anterior and/or posterior vaginal wall prolapse.…”
Section: Introductionmentioning
confidence: 99%
“…The levator ani is visible as a multilayer hyperechoic sling at this level. 10 The most caudal portion of the scan reveals the superficial perineal muscles, the perineal body and lower anal canal (Figure 11). Alignment of the pelvic organs (bladder neck or urethra, vagina and rectum or anal canal) indicates that the levator plate is intact, and the arched symmetrical appearance pubic bone is a useful landmark to check that scan has been performed in a neutral position.…”
Section: Three-dimensional Cross-sectional Viewmentioning
confidence: 99%
“…To assess surgical outcome and postoperative complications, the patients' subjective rating is combined with clinical examination and ultrasound imaging. Current imaging modalities reach their limits, however, when they are used to evaluate the mesh arms and their fixation point, especially when trying to verify a correct location or diagnosing misplacement [8]. …”
Section: Introductionmentioning
confidence: 99%